Synthesis of Bimetallic Metal-Organic Frameworks (MOFs) La-Y-PTC for Enhanced Dyes Photocatalytic Degradation - Adawiah Adawiah; Muhammad Shofyan Gunawan; Isalmi Aziz; Wulandari Oktavia (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Metal-Organic Frameworks (MOFs) is widely utilized as photocatalysts in dye photocatalytic degradation. This study successfully synthesized bimetallic MOFs La-Y-PTC by the solvothermal method. The synthesized La-Y-PTC has a diffractogram pattern with a value of 2θ = 5.69°; 9.57°; 16.8°; 20.05°; 24.8°; 26.15°; 29.77° and 41.93° with a crystal size of 21.45 nm. The La-Y-PTC has symmetric and asymmetric (COO−) at 1591 and 1433 cm−1, La−O and Y−O groups at 596 and 659 cm−1 and a band gap energy of 2.16 eV. Scanning Electron Microscope analysis showed that the morphology of La-Y-PTC is spherical with a particle size of 354.307 nm. La-Y-PTC degrades methylene blue and methyl orange at pH 2 with a degradation efficiency of 69.57% and 93.63%, respectively, under 250 watts of mercury lamp irradiation for 180 min with hydroxyl radical species as a dominant species that play a role in methylene blue and methyl orange degradations. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).